Analisis Strategi Pemasaran UMKM Minuman Es Teh Tamsos - Akbar Maulana; Istianah Setyaningsih (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze the marketing strategies implemented by the UMKM (Micro, Small, and Medium Enterprises) Es Teh Tamsos in facing competition, the supporting factors for success, the challenges encountered, and the influence of marketing strategies on customer loyalty and satisfaction. This research uses a qualitative approach with a case study method, where data were collected through in-depth interviews with the owner, employees, and customers, supported by field observations and documentation. The findings reveal that Es Teh Tamsos applies a marketing mix strategy (product, price, promotion, and distribution) in a simple yet effective manner, focusing on its unique taste, affordable pricing, direct and digital promotions, as well as strategic distribution near campuses and public areas. The key supporting factors include product quality, customer loyalty, strategic location, and digital promotion support, while the main challenges consist of limited capital, intense competition with similar brands, human resource constraints, and shifting consumer trends. These results reinforce Kotler & Armstrong’s theory on the importance of aligning marketing strategies with target market segments and support previous studies highlighting the role of product quality and affordable pricing in enhancing customer loyalty within small businesses.